Sports medicine : just the facts - O'Connor, Francis G. (McGraw-Hill, Medical Pub. Division, 2005)
"Ideal for anyone who cares for patients with sports-related conditions - from specialists to primary care clinicians. Content is organized according to the material tested on the American Board of Family Practice Sports Medicine examinations. Standardized, bulleted format emphasizes key points of epidemiology, pathophysiology, clinical features, diagnosis and differential, and treatment. Covers the entire spectrum of sports medicine - from the pre-participation examination to medical and musculoskeletal conditions, emergency care, diagnostic imaging, rehabilitation, and much more. Sports-specific chapters cover everything from golf to rugby, gymnastics to wrestling. Separate chapters address special populations including the elderly, pediatric, female, special, and disabled athlete, as well as athletes with cancer or HIV."--BOOK JACKET.